Clinicopathological and Prognostic Significance of CD47 Expression in Lung Neuroendocrine Tumors - Mario Orozco-Morales; Alejandro Avilés-Salas; Norma Hernández-Pedro; Rodrigo Catalán; Graciela Cruz-Rico; Ana Laura Colín-González; Elsa Dosal-Mancilla; Pedro Barrios-Bernal; Oscar Arrieta (Journal of Immunology Research)
Background. Lung neuroendocrine tumors account for approximately 15% of all lung cancer cases. LNET are subdivided into typical carcinoid (TC), atypical carcinoid (AC), large cell neuroendocrine carcinoma (LCNEC), and small-cell lung cancer (SCLC). The Ki-67 index has been used for decades to evaluate mitotic counts however, the role of Ki-67 as a biomarker for assessing prognosis and guiding therapy in metastatic LNET still lacks feasible clinical validation. Recent clinical trials have indicated that inhibition of CD47 with anti-CD47 antibodies exerts a promising antitumor effect against several human malignancies, including NSCLC, melanoma, and hematologic malignancies. However, the clinical relevance of CD47 expression in LNET has remained unclear. Methods. We performed a retrospective study in which we analyzed tumor biopsies from 51 patients with a confirmed diagnosis of LNET that received treatment at our hospital. Then, we analyzed if there was any correlation between CD47 expression with any clinical or pathological characteristic. We also analyzed the prognostic significance of CD47, assessed as progression-free survival and overall survival. Results. A total of 51 patients with LNET were enrolled in our study. The mean age at diagnosis was 57.6 (±11.6) years; 30 patients were women (59%). 27.5% of patients were positive for CD47 expression, and 72.5% of patients showed a CD47 expression of less than 1% and were considered as negatives. In patients with high-grade tumors (this time defined as Ki‐67>40%), the positive expression of CD47 was strongly associated with an increased PFS. Albeit, these differences did not reach statistical significance when analyzing OS. Conclusion. Contrary to what happens in a wide range of hematologic and solid tumors, a higher expression of CD47 in patients with LNET is associated with a better progression-free survival, especially in patients with a Ki‐67≥40%. This “paradox” remains to be confirmed and explained by larger studies.